PREPARATION AND CHARACTERIZATION OF LAFUTIDINE AS IMMEDIATE RELEASE ORAL STRIP USING DIFFERENT TYPE OF WATER-SOLUBLE POLYMER - Jabir, Saba Abdulhadee; Sulaiman, Halah Talal (International Journal of Applied Pharmaceutics, 2018)
Objective: The objective of the present study was to design and optimize oral fast dissolving film (OFDF) of practically insoluble drug lafutidine in order to enhance bioavailability and patient compliance especially for a geriatric and unconscious patient who are suffering from difficulty in swallowing. Methods: The films were prepared by a solvent casting method using low-grade hydroxyl propyl methyl cellulose (HPMC E5), polyvinyl alcohol (PVA), and sodium carboxymethyl cellulose (SCMC) as film forming polymers. Polyethylene glycol 400 (PEG400), propylene glycol (PG) and glycerin were used as a plasticizer to enhance the film forming properties of the polymer. Tween 80 (1% solution) and poloxamer407 were used as a surfactant, citric acid as a saliva stimulating agent, and croscarmellose as a super disintegrant. Films were then tested for both physical (weight variation, thickness, surface pH, drug content) and mechanical (folding endurance, tensile strength, percent elongation, Young's modulus) characteristics. In vitro disintegration, time and drug release profile were also determined for each formula. Results: Films were found to be satisfactory when evaluated for both physical and mechanical characterizations. The surface pH of all the films was found to be within the range of salivary pH 6.8. The USP dissolution apparatus type II (paddle type) was used for in vitro drug release studies. The optimized formulation F13 gave 100 % of drug released at 2 min. It also showed satisfactory surface pH (6.2±0.2), drug content (100.1±0.01%), the disintegration time of (7.0±0.5) seconds and the time needed for 80% of medication to be released (T80%) was 0.96 min. Conclusion: Lafutidine OFDF was formulated using HPMC E5 as film-forming a polymer with PEG400 as a plasticizer. Combination of tween80 (1% solution) and poloxamer407 as a surfactant were used in the presence of croscarmellose as a super disintegrant. The chosen OFDF disintegrates within seven seconds, releases the drug rapidly and gives an action.